Gestión de ventas de la Distribuidora Touma S.A Ditosa en la ciudad de Babahoyo durante el periodo 2022. - Murillo Monserrate, Brithany Anahiz (2023)
The case study at Distribuidora Touma S.A Ditosa reveals critical challenges in inventory and liquidity management during the years 2021 and 2022. The results, supported by financial indicators and the application of IAS 2 on inventory measurement, highlight the urgency to address these issues to ensure the company's long-term operational efficiency and profitability. In terms of inventory management, a significant decrease in inventory turns and an increase in sales days in inventory are seen in 2022 compared to 2021. This indicates that products are selling at a slower rate and remain in stock. the warehouse for longer, which could increase storage costs and decrease profitability. The conclusions are based on the established objectives and emphasize the need to address the challenges in inventory management. The implementation of an efficient inventory control system and more precise replenishment policies is recommended. Regarding liquidity, there has been a slight improvement in the Current Ratio and the Quick Ratio or Acid Test in 2022 compared to 2021. However, this improvement must be balanced with inventory management. It is suggested that cost-benefit analyzes be performed before implementing significant changes in inventory management.